KEPASTIAN HUKUM KEWENANGAN KOMISI PEMBERANTASAN KORUPSI DALAM RANGKA UPAYA MENINGKATKAN PEMBERANTASAN TINDAK PIDANA KORUPSI - Winerdi, Yos; Hedwig Adianto Mau,; Kresna Menon, (Journal of Innovation Research and Knowledge, 2025)
Corruption is a disgraceful act that severely undermines Indonesia’s national economy. As such, corruption-related offenses must be eradicated through precise and effective legal mechanisms; otherwise, such efforts would be rendered ineffective. In pursuit of this objective, this study examines the extent of the Corruption Eradication Commission’s (Komisi Pemberantasan Korupsi, KPK) authority following the enactment of Law Number 19 of 2019 concerning the Corruption Eradication Commission, as well as the optimization of legal certainty regarding its authority to enhance anti-corruption efforts in Indonesia. This research adopts a descriptive approach concerning the legal certainty of KPK’s authority in strengthening corruption eradication efforts. The study employs a normative juridical analysis (qualitative) method, focusing on the fundamental legal issues surrounding KPK’s powers. The findings reveal that the amendments introduced by Law Number 19 of 2019, which revised Law Number 30 of 2002, have significantly altered the institutional framework and authority of KPK. These legislative changes have led to a considerable decline in KPK’s effectiveness, as reflected in Indonesia’s Corruption Perception Index (CPI), which has shown a substantial downward trend over the fiveyear period from 2019 to 2024. This decline is largely attributed to the absence of legal certainty in KPK’s authority, which has hindered its ability to execute its functions effectively. To address this issue, it is imperative to strengthen the legal certainty of KPK’s authority through legislative reforms that clarify its powers and institutional structure. This may be achieved by repositioning KPK as an independent state institution or by granting it constitutional legitimacy through direct recognition under the 1945 Constitution of the Republic of Indonesia